(untitled) (Al-Mansour Journal, 2022)
This study aims to examine three kinds of rehabilitation techniques which are Carbon Fiber Reinforced Polymer “CFRP” Internal sheets, CFRP jacketing, and Slurry infiltrated Fiber Concrete “SIFCON” jacketing. The experimental program involved casting six specimens of R.C beam-column joints. These specimens are rehabilitated by the proposed techniques and retested. Three of these specimens are rehabilitated by SIFCON jacketing with different levels of jacket thickness and steel fibers. All the specimens (before and after rehabilitation) were tested under the repeated load of three cycles every 400 kN till failure. The specimens consisted of beam and column of 600mm and the joint area is 400mm by 400mm. The results showed that all the techniques were efficient in the recovery of the original structural properties of R.C joints. The CFRP internal sheets recover 144.49 % of maximum strength and 141.57% for yielding load while CFRP jacketing recovers 142.86% and 189.87%. While the SIFCON jacketing recovers about 170.71% to 188.14% of maximum strength and about 214.15% to 249.71% to 226.58% of yielding load respectively for all the proposed steel fibers content and jacket thickness. The recovery of original levels of maximum and yielding deflection about 32% and 50% respectively, also recovery in the stiffness factor.